The Struggle between Customary Law and Islamic Law in the Distribution of Inheritance of Melayu Communities on the Indonesia-Malaysia Border in Sambas, West Kalimantan - Asman Asman (Universitas Sultan Ageng Tirtayasa, 2026)
The revelation of the verses of the Qur'an regarding inheritance affirms that men and women have equal status as heirs, as stipulated in Surah An-Nisa verses 11-12. This provision reflects the principle of justice in Islamic law through the recognition and protection of women's rights. However, in the social practices of the Malay inland community of Sambas, there is still a discrepancy between Islamic legal norms and customary practices. The distribution of inheritance tends to be carried out equally between boys and girls, on the grounds of social justice and equality, without referring to the proportional provisions in sharia. This study is a field study with a phenomenological approach to understand the construction of the meaning of justice in the inheritance practices of Malay border communities. The results show that equal distribution of inheritance is considered fair because it aligns with cultural values, family solidarity, and the collective conscience of the community. This tradition has been deeply rooted and has gained social legitimacy across generations. The research gap in this study lies in the lack of studies that specifically examine the dialectic between Islamic inheritance law and customary practices in Malay border communities, especially from the perspective of subjective experience and the construction of the meaning of local justice. The novelty of this research lies in its interpretive analysis of local culturally based concepts of justice interacting with sharia norms, resulting in a new understanding of how border communities reconstruct inheritance justice amidst the tension between normative texts and social reality.